QUANTIFICAÇÃO DE MACRO E MICROELEMENTOS EM COLÍRIOS LUBRIFICANTES UTILIZADOS NO TRATAMENTO DA DOENÇA DO OLHO SECO - Marcelo de Oliveira (2024)
Dry eye is a multifactorial disease of the ocular surface characterized by loss of tear film homeostasis and is usually accompanied by ocular symptoms. The disease affects millions of people around the world, it is one of the most common reasons for consulting an ophthalmologist and conventional treatment uses lubricating eye drops or artificial tears, which can be effective in mild and moderate cases. The objective of this study was to evaluate the presence of macro and microelements in lubricating eye drops used to treat dry eye disease in Brazil. After digestion in an open system, the concentrations of Al, As, Ba, Cd, Co, Cu, Cr, Pb, Fe, Mg, Mn, Mo, Ni, Se, V and Zn were determined in 19 samples of lubricating eye drops using the technique of Inductively Coupled Plasma Optical Emission Spectrometry (ICP OES). The limit of detection (LOD) and limit of quantification (LOQ) values for the quantified elements were, respectively: Al (0.0363 µg/g, 0.1211 µg/g), As (0.0036 µg/g, 0.0121 µg/g), Ba (0.0003 µg/g, 0.0010 µg/g), Cd (0.0005 µg/g, 0.0018 µg/g), Co (0.0010 µg/g , 0.0033 µg/g), Cr (0.0011 µg/g, 0.0037 µg/g), Cu (0.0020 µg/g, 0.0067 µg/g), Fe (0.0065 µg/g g, 0.0217 µg/g), Mg (0.0017 µg/g, 0.0057 µg/g), Mn (0.0002 µg/g, 0.0007 µg/g), Mo (0.0006 µg /g, 0.0019 µg/g), Ni (0.0011 µg/g, 0.0038 µg/g), Pb (0.0050 µg/g, 0.0168 µg/g), Se (0.0045 µg/g, 0.0149 µg/g), V (0.0010 µg/g, 0.0032 µg/g) and Zn (0.0016 µg/g, 0.0052 µg/g). The elements Al (2.382 µg/g), As (0.204 µg/g), Ba (0.056 µg/g), Cd (0.051 µg/g), Co (1.085 µg/g), Cr (0.020 µg/g), Cu (0.023 µg/g), Fe (0.453 µg/g), Mg (24.284 µg/g), Mn (0.014 µg/g), Mo (0.046 µg/g), Ni (0.071 µg/g), Pb ( 0.049 µg/g), Se (0.365 µg/g), V (0.083 µg/g) and Zn (0.552 µg/g) presented the highest concentration values. Furthermore, concentrations were compared with the levels established by the Brazilian Pharmacopoeia (FB) and ICH Q3D (R2) guideline of the International Council for Harmonization of Technical Requirements for Medicinal Products for Human Use (ICH) for parenteral use. Daily exposure from eye drop instillation was compared with the parenteral permitted daily exposure (PDE) defined in the ICH Q3D (R2) guideline. Regarding the parenteral route, the concentration of As (5 samples) and Cd (3 samples) was higher than those allowed by FB. Two samples showed concentrations of As and Cd above the limit allowed by FB in the parenteral route. The Co content in a sample was higher than the concentration value allowed by the ICH Q3D (R2) guideline in the parenteral route. Based on the ICH Q3D (R2) guideline, exposure values for the chemical elements As, Ba, Cd, Co, Cr, Cu, Mo, Ni, Pb, Z and V were below the limit established by the ICH Q3D (R2) guideline via the parenteral route. However, short or long-term exposure to this type of medicine containing high levels of these elements represents a health risk. The presence of macro and microelements in eye drops is a warning to regulatory agencies in several countries to carry out controls and inspections.